Isolation and identification of lactobacillus sp. from fresh fruits / Siti Mas Nur Ain Mazlan - Mazlan, Siti Mas Nur Ain (2017)
Lactic Acid Bacteria has been widely studied in dairy products. However, the presence of Lactic Acid Bacteria (LAB) in fruits has rarely been focused. Fruits contain organic acids and rich with nutrients such as minerals, carbohydrates, nitrogen compounds and a low pH environment that are suitable for the growth of Lactobacillus sp. The objectives of this study were to isolate and identify Lactobacillus sp. from fresh fruits by using molecular techniques which is Polymerase Chain Reaction (PCR) method. The white colony from MRS agar was isolated from banana and red dragon fruits. The phenotypic method was used to confirm the shapes and color of Lactic Acid Bacteria (LAB) which is Gram positive bacteria with rod or coccus shaped. The PCR results showed the identification of Lactobacillus sp. are at 216 bp by using the specific primer which is Lacto-16S-R and Lacto-16S-F. The results also indicate that Polymerase Chain Reaction (PCR) is more efficient to detect the strains of bacteria and give highly specific results.